Analisis Pengaruh Peningkatan Gain Terhadap Suhu Lingkungan Pada Antena Mikrostrip Array 2.4 Ghz - Aisah Aisah; Rudy Yuwono; Bagus Julianto (Jurnal EECCIS, 2018)
Abstract - This research proposed design and manufacturing two microstrip antennas arrays resonated at 2.4 GHz frequency. This research analyzing the effect of increasing the antenna gain to the environment temperature. The antenna uses a two-layer substrate FR-4 (dielectric constant = 3.9) and a copper conductor material. Antenna design and simulation is done by using CST Microwave Studio 2014 program. The simulation result of the five microstrip antennas has VSWR below 2 at 2.4 GHz frequency with S11 value (Return Loss) ≤ -10 dB, axial ratio above 10 dB and has Gain value above 2 dBi and 10 dBi for antenna array.